2021
DOI: 10.4103/wjnm.wjnm_116_20
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in anorectal melanoma

Abstract: To evaluate the diagnostic role of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) in initial staging and restaging of anorectal melanoma. This was a single-institution, retrospective observational study; patients for initial staging and with clinical or radiological suspicion of disease recurrence referred for PET/CT between January 2006 and December 2015 were included in the study. Diagnostic performance of PET/CT was evaluated for baseline staging and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…During the full text review of the remaining 372 articles, 269 were considered ineligible based on the above-mentioned selection criteria. Finally, 100 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the full text review of the remaining 372 articles, 269 were considered ineligible based on the above-mentioned selection criteria. Finally, 100 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ...…”
Section: Resultsmentioning
confidence: 99%
“…Based on the limited literature we found on this subject, [ 18 F]F-FDG PET may be of benefit in mucosal melanoma. In a study by Bakare et al [ 22 ] investigating patients with anorectal melanoma, [ 18 F]F-FDG PET/CT showed a sensitivity of 97%, specificity of 100%, and accuracy of 97% in detecting primary lesions in initial staging. Regional nodal involvement was correctly detected in 46/61 patients, with a false result (false negative) in only one case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations